Canine and feline abdominal arterioportal communications can be classified based on branching patterns in computed tomographic angiography. Issue 6 (21st September 2018) - Specchi, Swan; Rossi, Federica; Weisse, Chick; Morabito, Simona; Petrovitch, Nicholas P.; Drees, Randi; Thierry, Florence; Ricciardi, Mario; Penchome, Rampaipat; Armenise, Andrea; Pey, Pascaline; Paek, Matthew; et al.
Abstract: Arterioportal vascular anomalies are communications between the splanchnic arteries and the portal system that represent a rare cause of presinusoidal portal hypertension in small animals. There is little information concerning the imaging findings of arterioportal communications in small animals and no classification could be found for radiologists and surgeons. The aims of this retrospective descriptive multicentric study were to describe the computed tomographic characteristics of arterioportal communications in a group of cats and dogs, and to propose a classification based on computed tomography (CT) angiographic anatomy. Computed tomography databases from multiple veterinary hospitals were searched for cats and dogs with a diagnosis of arterioportal communication. A total of 36 animals (33 dogs, three cats) met the inclusion criteria. There were 32 intrahepatic arterioportal malformations and four extrahepatic fistulae. The intrahepatic arterioportal malformations were classified as right divisional (11/32) and left divisional (21/32), and the left divisional were subclassified as left medial (16/21) and left lateral (4/21). One patient showed multiple intrahepatic arterioportal communications with concomitant left medial and left lateral conformations. Two patients with intrahepatic arteriovenous malformation showed concomitant congenital intrahepatic shunts. The proposed anatomical classification based on CT angiography could allow veterinary radiologists to have a more systematic approach and help improve the radiologist–surgeon communication.